Synthesis, characterization and anticancer activity of mono- and dinuclear Ni(II) and Co(II) complexes of a Schiff base derived from o-vanillin. (15th March 2019) - Bahron, Hadariah; Khaidir, Siti Solihah; Tajuddin, Amalina Mohd; Ramasamy, Kalavathy; Yamin, Bohari M.
Graphical abstract: The Schiff base ligand LA was reacted with nickel(II) acetate and cobalt(II) acetate in different L:M ratios and under different reaction conditions, resulting in mononuclear and dinuclear complexes of both metals. Characterization was carried out via physicochemical and spectral techniques, including single crystal X-ray crystallography for Ni(LA). The Ni(II) centre has a distorted square planar geometry, with the ligand acting as a tetradentate ONNO chelate. There are 4 asymmetric units, each containing one water molecule of crystallization and one Ni(LA) complex, in a unit cell. All the compounds were screened for anticancer activity against HCT116 cell lines and Ni(LA) emerged as the most potent compound with the lowest IC50 value of 0.81 mM. The order of anticancer potency was Ni2 (LA) > Ni(LA) > LA > Co2 (LA) > Co(LA). Abstract: A Schiff base ligand, 6, 6′-dimethoxy-2, 2′-[ o -phenylenebis(nitrilomethylidyne)]diphenolato (LA), and its mononuclear and dinuclear Ni(II) and Co(II) complexes were synthesized. Structural elucidation was carried out via elemental analysis, molar conductivity, IR, NMR, UV–Vis spectroscopy, TGA and magnetic susceptibility. Single crystal X-ray diffraction of the Ni(LA) complex revealed a square planar geometry of the Ni(II) centre, with the ligand acting as a tetradentate ONNO chelate. Upon coordination to the metal centers, the ν (CN) and ν (CO) peaks shifted to lower frequencies, with appearance of new peaks assignable to ν (MN) and ν (MO) in the ranges 535–560 and 421–460 cm −1, respectively. Ni(LA) and Ni2 (LA) complexes are diamagnetic, whereas the Co(LA) and Co2 (LA) complexes are paramagnetic with 3 unpaired electrons each. All the complexes displayed low molar conductivities in acetonitrile indicating non-electrolytic behavior. Anticancer screening against human colorectal cancer HCT116 cell lines revealed that both dinuclear complexes were more active than their mononuclear counterparts. Ni2 (LA) showed the highest potency with an IC50 value of 0.81 μM.